Spectral and structural analysis of large Stokes shift fluorescent protein dKeima570 - Xu, Yongbin; Hwang, Kwang Yeon; Nam, Ki Hyun (The journal of microbiology, 2018)
The Keima family comprises large Stokes shifts fluorescent proteins, which are useful for dual-color fluorescence crosscorrelation spectroscopy and multicolor imaging. dKeima570 belongs to the Keima family. It has a unique chromophore sequence composed of CYG with an emission peak at 570 nm, but its molecular properties are unclear. We report the spectral analysis of dKeima570 and its crystal structure at 2.0 Å resolution. The dKeima570 chromophore is mainly in the protonation state in the entire pH range. The pH-induced non-fluorescence state was observed below pH 4.0. The crystal structure of the dKeima570 chromophore has a cis conformation at pH 6.5. The chromophore is surrounded by a unique hydrogen bonding network containing a water bridge between Glu212 and Arg194. The analysis of the dimeric interface of dKeima570 revealed the key residues that maintain the oligomerization of Keima family. Structural comparisons of dKeima570 and mKeima provided insights into the unique large Stokes shifts characteristics of the Keima family.